Akwé: Kon -ohjeiden vaikutus saamelaisnäkökulman huomioimiseen Hammastunturin erämaa-alueen hoito- ja käyttösuunnitelmassa - Meriläinen, Sara (Helsingfors universitet, 2015)
The Akwé: Kon Guidelines, based on the Article 8(j) of the Convention on Biological Diversity, are voluntary guidelines for cultural, environmental and social impact assessment. The Guidelines are intended to be applied in the impact assessments of plans and projects conducted in areas that are inhabited or used by indigenous populations or that contain sacred places of indigenous peoples. The Guidelines have been applied for the first time ever in Finland in Hammastunturi wilderness area. The research question of the thesis is 'To what extent the Akwé: Kon Guidelines have affected on the consideration of Sami perspective in the management plan of Hammastunturi wilderness area'. The data of the thesis consists of two management plans of Hammastunturi wilderness area published in different years. In the new plan the Akwé: Kon Guidelines have been applied whereas in the old plan the Guidelines have not been used. The management plans produced by the Finnish forest administrator Metsähallitus are secondary data. The qualitative research methods used in the thesis are comparative content analysis and thematic analysis. As a result of the content analysis four themes about the consideration of Sami perspective came up from the data. The themes are Sami perspective in the structure of the plans, attitude towards the indigenous people, values and the actions presented in the plans. The key differences of the new plan compared to the old plan are that the Sami people are concerned more extensively in the context of cultural heritage and traditional livelihoods, the Sami people are referred to as an indigenous people, the Sami culture is defined as a cultural value of the area and the new plan contains actions that directly aim at the protection of Sami culture. The conclusions are that in the new plan the Sami perspective is integrated into the other sections better than in the old plan. In addition, the Sami people are considered as an indigenous people and not as a minority. Contrary to the old plan, in the new plan ...